Genome characterization and phylogenetic analysis of scale drop disease virus isolated from Asian seabass (Lates calcarifer) - Chokmangmeepisarn, Putita; Azmai, Mohammad Noor Amal; Domingos, Jose A.; van Aerle, Ronny; Bass, David; Prukbenjakul, Pochara; Senapin, Saengchan; Rodkhum, Channarong (Multidisciplinary Digital Publishing Institute, 2024)
Scale drop disease virus (SDDV), a double-stranded DNA virus in the family Iridoviridae, has been reported widely in southeast Asian countries as a causative agent of scale drop syndrome (SDS) in Asian seabass. SDS has resulted in high mortality and significant economic losses to the aquaculture industry. This study demonstrated the use of metagenomic methods to investigate bacterial and viral communities present in infected fish tissues and recover a complete genome of the causative agent named SDDV TH7_2019. Characterization of the TH7_2019 genome revealed a genome size of 131 kb with 134 putative ORFs encoding viral proteins potentially associated with host apoptosis manipulation. A comparative genome analysis showed a high degree of amino acid identity across SDDV strains, with variations in number of repeat sequences and mutations within core genes. Phylogenetic analyses indicate a close relationship among SDDV genomes. This research enhances our understanding of the genetic diversity and evolutionary relationship of SDDV, contributing valuable insights for further development of effective control strategies of SDDV.